Strategi Pengembangan Pariwisata Kabupaten Jepara - Septiana Novitasari; Slamet Santoso; Rihandoyo Rihandoyo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to identify and assess the tourism development strategy undertaken by the department of tourism and culture district of Jepara, and to recommend new strategies in Jepara district tourism development. Based on the results of the study indicate that tourism development strategy undertaken by the department op tourism and culture has not quite succeeded in Jepara district, while there are some indicators which is considered very successful, but more will be considered less successful writers. The conclusions of this study is the overall tourism development strategy Jepara District by the Department of Tourism and Culture District of Jepara has not succeeded. The writers recommends strategies to improve the strategy has not been successful.